2022
DOI: 10.1103/physreva.105.023301
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-geometric perspective on spin-orbit-coupled Bose superfluids

Abstract: We employ the Bogoliubov approximation to study how the quantum geometry of the helicity states affects the superfluid properties of a spin-orbit-coupled Bose gas in continuum. In particular we derive the low-energy Bogoliubov spectrum for a plane-wave condensate in the lower helicity band and show that the geometric contributions to the sound velocity are distinguished by their linear dependences on the interaction strength; that is, they are in sharp contrast to the conventional contribution which has a squa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In addition, the aspect ratio is easily adjusted by manipulating the trap frequency. It has been shown that the trap geometry issue has been widely discussed in recent years [39,40]. We point out that the discussions above are confined to isotropy SOC strength.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, the aspect ratio is easily adjusted by manipulating the trap frequency. It has been shown that the trap geometry issue has been widely discussed in recent years [39,40]. We point out that the discussions above are confined to isotropy SOC strength.…”
Section: Resultsmentioning
confidence: 93%